PENERAPAN MODUL AJAR PERSAHABATAN (1 SAMUEL: 18:1-5) BERKARAKTERISTIK NON-SMART DI SDN 1 SABARU PALANGKARAYA - Ribka Wahyu Christiani; Sari; Mantilie; Yumi (CV. ADIBA AISHA AMIRA, 2025)
This research aims to examine the implementation of a teaching module with the theme of friendship based on the story of David and Yonatan (1 Samuel 18:1-5) at SDN 1 Sabaru Palangkaraya. This teaching module is designed with non-SMART characteristics, which does not focus on specific, measurable or time-limited learning objectives, but rather on developing character and moral values ​​through stories. The aim of this research is to explore the effect of implementing this teaching module on students' understanding and attitudes in establishing genuine friendships, as well as fostering positive character values. This research uses a qualitative approach with a case study design, involving interviews, classroom observations, and document analysis to explore the impact of using teaching modules on student attitudes and behavior at SDN 1 Sabaru Palangkaraya.